2017
DOI: 10.1038/s41598-017-11333-7
|View full text |Cite
|
Sign up to set email alerts
|

Logical gates in actin monomer

Abstract: We evaluate information processing capacity of a single actin molecule by calculating distributions of logical gates implemented by the molecule via propagating patterns of excitation. We represent a filamentous actin molecule as an excitable automaton network (F-actin automaton). where every atom updates its state depending on states of atoms its connected to with chemical bonds (hard neighbours) and atoms being in physical proximity to the atom (soft neighbours). A resting atom excites if a sum of its excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…We implemented several concrete implementations of logical gates and functions on a single actin filament [48] and on an intersection of several actin filaments [49] via collisions between solitons. We also used a reservoir-computing-like approach to discover functions on a single actin unit [50] and royalsocietypublishing.org/journal/rsos R. Soc. open sci.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented several concrete implementations of logical gates and functions on a single actin filament [48] and on an intersection of several actin filaments [49] via collisions between solitons. We also used a reservoir-computing-like approach to discover functions on a single actin unit [50] and royalsocietypublishing.org/journal/rsos R. Soc. open sci.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution demonstrates frequencies of discoveries of the fourinput-one-output logical gates and could be used for characterisation of a computational power of the fungal substrates. This is accompanied by distributions of gates discovered in experimental laboratory reservoir computing with slime mould Physarum polycephalum [18], succulent plant [8] and numerical modelling experiments on computing with protein verotoxin [3], actin bundles network [9], and actin monomer [4]. The distributions of gates discovered in natural systems are alike to each other in the hierarchies of the gates frequencies.…”
Section: Spikes Derived Logical Gatesmentioning
confidence: 91%
“…Figure 6. Comparative ratios of Boolean gates discovered in mycelium network analysed in present paper, black disc and solid line; slime mould Physarum polycephalum[18], black circle and dotted line; succulent plant[8], red snowflake and dashed line; single molecule of protein verotoxin[3], light blue '+' and dash-dot line; actin bundles network[9], green triangle pointing right and dash-dot-dot line; actin monomer[4], magenta triangle pointing left and dashed line. Area of xor gate is magnified in the insert.…”
mentioning
confidence: 86%
“…Computational studies discussed the feasibility of implementing Boolean gates on a single actin filament 31 and on an intersection of several actin filaments 32 via collisions between solitons. Further studies applied a reservoir-computing-like approach to discover functions on a single actin unit 33 as well as filament 34 . In 2016, for instance, we demonstrated that it is possible to implement logical circuits by linking the protein chains 32 .…”
Section: Introductionmentioning
confidence: 99%